Increasing Purchases of Environmentally Friendly Products through Green Advertising and Green Brand Awareness: The Role of Green Brand Image Mediators - Indratno, Diana Leli; Shalahuddin, Shalahuddin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to explore how green advertising and green brand awareness influence green brand image and its impact on green purchase behaviour among Generation Z in Indonesia, while also examining the moderating role of green product innovation in the dynamics of green product marketing and young consumer behaviour. The method used is quantitative with a survey of 250 Generation Z respondents, analysed using structural equation modelling (SEM) with AMOS-24. The main variables include green advertising, green brand awareness, green brand image, green product innovation, and green purchasing behaviour. The results show that green advertising and green brand awareness have a direct positive impact on green brand image, which in turn influences green purchasing behaviour, while green product innovation does not moderate this relationship. The research model proved to be statistically fit, emphasising the dominance of brand communication factors over product innovation in shaping Generation Z's perceptions. These findings provide practical recommendations for companies to emphasise green communication strategies, enhance advertising credibility, and strengthen green brand image to encourage the purchase of environmentally friendly products, as well as highlighting the importance of promoting sustainability to change the consumption patterns of the younger generation, which has a positive impact on the environment and sustainable development.